Rivers as carriers and potential sentinels for Burkholderia pseudomallei in Laos - Zimmermann, R; Ribolzi, O; Pierret, A; Rattanavong, S; Robinson, M; Newton, P; Davong, V; Auda, Y; Zopfi, J; Dance, D (Nature Publishing Group, 2018)
Burkholderia pseudomallei, causative agent of the often fatal disease melioidosis, dwells in tropical soils and has been found in freshwater bodies. To investigate whether rivers are potential habitats or carriers for B. pseudomallei and to assess its geographical distribution in Laos, we studied 23 rivers including the Mekong, applying culture-based detection methods and PCR to water filters and streambed sediments. B. pseudomallei was present in 9% of the rivers in the dry season and in 57% in the rainy season. We found the pathogen exclusively in Southern and Central Laos, and mainly in turbid river water, while sediments were positive in 35% of the B. pseudomallei-positive sites. Our results provide evidence for a heterogeneous temporal and spatial distribution of B. pseudomallei in rivers in Laos with a clear north-south contrast. The seasonal dynamics and predominant occurrence of B. pseudomallei in particle-rich water suggest that this pathogen is washed out with eroded soil during periods of heavy rainfall and transported by rivers, while river sediments do not seem to be permanent habitats for B. pseudomallei. Rivers may thus be useful to assess the distribution and aquatic dispersal of B. pseudomallei and other environmental pathogens in their catchment area and beyond.